(untitled) - Biderman, Charles (Hoboken, NewJersey, 2005)
Whether you are an investment professional managing billions of dollars or an individual investor with a small nest egg, TrimTabs Investing shows you how to beat the major stock market averages with less risk. This groundbreaking book begins by comparing the stock market to a casino in which the house (public companies and the insiders who run them) buys and sells shares with the players (institutional and individual investors). TrimTabs Investing argues that stock prices are primarily a function of liquidity—the amount of shares available for purchase and the amount of money available to buy them—rather than fundamental value. Finally, it outlines the building blocks of liquidity theory and explains how you can use them to predict the direction of the stock market.
Keywords: Stocks,Investment analysis,Stock exchanges,Cổ phiếu,Phân tích đầu tư,Thay đổi cổ phiếu; United States,United States,Hoa Kỳ,Hoa Kỳ